Ceramics and composites processing methods - Bansal, Narottam P.; Boccaccini, A. R. (Aldo R.) (Hoboken, N.J. : John Wiley & Sons, 2012)
'There is increasing interest in the application of ceramic materials in areas as diverse as transport, energy, environment and health. To address this trend, this single-source text supplies information on various processing and fabrication methods for advanced ceramics and ceramic composites with state-of-the-art research on methods, approaches, and techniques available for their processing and fabrication. A must-have for anyone pursuing this field, Processing of Ceramics and Composites tackles innovative technologies advancing the growing need for more reliable ceramic materials'--
'This is a comprehensive handbook of all the processing and fabrication methods for advanced ceramics and ceramic composites. Each chapter in the book is written by specialists and internationally renowned researchers in the field, and provides state-of-the-art research on methods, approaches, and techniques available for processing and fabrication of advanced ceramics and composites. It addresses materials heretofore uncovered by the literature, such as nanoceramics. The book includes a wide range of processing techniques for ceramics and composites, including traditional fabrication routes as well as modern approaches that are being developed to meet the increasing demand for more reliable materials in general'--
Includes bibliographical references and index.
Keywords: Ceramic materials; Composite materials